2020
DOI: 10.1039/d0ra01110j
|View full text |Cite
|
Sign up to set email alerts
|

A Sm-MOF/GO nanocomposite membrane for efficient organic dye removal from wastewater

Abstract: A nanocomposite membrane composed of samarium metal-organic frameworks and graphene oxide nanosheets was fabricated for organic dye removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A known dose of UiO-66/ MIL-101(Fe)-GOCOOH composite (0.001-0.03 g) was added to MB dye (50 to 300 mg L À1 ). pH optimization (3)(4)(5)(6)(7)(8)(9)(10)(11) was adjusted using 0.01 M of NaOH and/or 0.01 M of HCl. The adsorption process was conducted at various temperatures (25-55 C) under constant agitation rate (250 rpm).…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A known dose of UiO-66/ MIL-101(Fe)-GOCOOH composite (0.001-0.03 g) was added to MB dye (50 to 300 mg L À1 ). pH optimization (3)(4)(5)(6)(7)(8)(9)(10)(11) was adjusted using 0.01 M of NaOH and/or 0.01 M of HCl. The adsorption process was conducted at various temperatures (25-55 C) under constant agitation rate (250 rpm).…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…For instance, methylene blue (MB) dye is mostly utilized for coloring cotton, wood and silk, but its discharge into water bodies even in low concentration leads to various harmful impacts such as eye burning, vomiting, cyanosis, convulsions, tachycardia and methemoglobinemia. 3,5 Accordingly, several techniques have been applied for dye removal such as advanced oxidation, 6 membrane separation, 7 electrolysis, 8 catalytic reduction, 9,10 photocatalytic degradation, 11 occulation. 12 Other than the mentioned techniques, visible light-driven photocatalysis and adsorption methods are considered the most promising technologies in the environmental remediation eld owing to their high efficiencies, low cost, minimal harmful by-products and their low energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The Sm-MOF/GO membrane had high water permeance (26 L m À2 bar À1 h À1 ) and a high adsorption capacity for RhB (491%) (Table 2). 191 It has been found that these MOF-based membrane investigations are limited to a few MOFs which have been applied for removal of a few dye molecules (MB, CR, MO, RhB, MG, etc. ), and only laboratory-scale short-term tests have been performed.…”
Section: Filtration Through Mof-based Membranesmentioning
confidence: 99%
“…The utilization of NPs based on a metal–organic framework (MOF) has received a lot of important attention lately, but it is primarily employed for drinking water and wastewater treatment [ 16 , 17 , 18 ]. Thus, there is a massive opportunity for scientists to envisage potential uses of MOF in soil remediation.…”
Section: Introductionmentioning
confidence: 99%